Economic Transformation and Business Opportunities in Asia - Hoontrakul, Pongsak (Springer International Publishing, 2018)
This book examines the uneven economy in Asia, showing how the pace of economic transformation affects prosperity and the emerging middle class. Using the Lewis turning point and the long run cycle of the rise and fall of nations as a framework, it demonstrates how demographic trends, digitalization rates and consumer preferences creates business opportunities in a disruptive and uncertain world. This includes moves toward promoting Eurasian integration, restructuring of state-owned enterprises, green economy, and the digital economies - ecommerce, fintech and sharing economy. Vanity capital, longevity and leisure economies are also discussed. The author explains what drives creative disruption, technical innovation and their effect on manufacturing, consumers, businesses, and sustainability. It is essential reading for students, academics, executives, and businesspersons wanting in-depth coverage of the economic landscape in Asia.